(untitled) (Arquivos do Mudi, 2023)
Hypertriglyceridemia is a predisposing factor for several metabolic diseases in the world today. Their cause is multifactorial, several factors are directly linked to the modification of plasma lipid metabolism, among them are genetics and exercise. The genic overexpression of apoCIII makes the animal hypertriglyceridemic and high levels of blood cholesterol, enabling further studies to be done on its metabolic profile. This study investigates how apoCIII overexpression and exercise modify the metabolism of genetically modified mice, especially their energy expenditure. We used 15-month-old male C57Bl/6 mice, subdivided into 4 groups: 2 NTG groups (non-transgenic mice that were submitted to training and their controls) and 2 CIII groups (transgenic Mice with basal triglyceridemia above 300mg/dL that were submitted to training and their controls). The exercised groups underwent for 8 weeks a moderate intensity training for 40 minutes 3 times a week. All animals were submitted to a stress test to evaluate performance and energy expenditure. The trained animals had higher energy expenditure during all stages of the test (p<0.01) and the area under curve of the EE showed that the trained animals had higher caloric consumption (p<0.001), while the animal CIII sed had a much higher energy expenditure than its control NTG sed (p<0.001). We conclude that dyslipidemia makes the CIII animal less fit for exercise, and trained animals have lower energy expenditure independent of dyslipidemia and produced more work.